Lessons of the month 1: Learning from Harvey; improving blood-taking by pointing the needle in the right direction - Dorrington, K; Frise, M (Royal College of Physicians, 2019)
The taking of blood for diagnostic purposes is a frequent cause of difficulty for physicians. In patients with intact visible or palpable large veins, such as those often seen in the antecubital fossa, a needle or cannula entering from any direction will usually be rewarded with any quantity of blood. In smaller veins in less convenient locations, such as in the hand, the direction of the needle becomes much more important. Failure to take blood is very commonly because of failure to appreciate the direction of flow of venous blood up the arm, and the ubiquitous presence of valves in the veins, both aspects of the circulation clearly described by William Harvey nearly 4 centuries ago. This paper encourages more frequent success with phlebotomy by remembering Harvey’s work and pointing the needle in the right direction; this is not always towards the heart.